All Questions Topic List
None Questions
Previous in All Question Next in All Question
Previous in None Next in None
Question Number 123144 by aurpeyz last updated on 23/Nov/20
∫x−16x−5−x2dx
Answered by benjo_mathlover last updated on 23/Nov/20
6x−5−x2=−5−(x2−6x)=−5−(x2−6x+9)+9=4−(x−3)2∅(x)=∫x−14−(x−3)2dxletx−3=2sinr;dx=2cosrdrx−1=2sinr+2∅(x)=∫2(sinr+1)(2cosrdr)4−4sin2r∅(x)=2∫(sinr+1)dr∅(x)=−2cosr+2r+c∅(x)=−2(4−(x−3)22)+2sin−1(x−32)+c∅(x)=−6x−5−x2+2sin−1(x−32)+c
Answered by Dwaipayan Shikari last updated on 23/Nov/20
∫x−36x−5−x2+2−(x2−6x+9)+4dx=−12∫6−2x6x−5−x2+2∫14−(x−3)2dx=−6x−5−x2+2sin−1x−32+C
Terms of Service
Privacy Policy
Contact: info@tinkutara.com